Comprehensivemolecular characterization of clear cell renal cell carcinoma - Creighton, C.; Morgan, M.; Gunaratne, P.; Wheeler, D.; Gibbs, R.; Robertson, A.; Chu, A.; Beroukhim, R.; Cibulskis, K.; Signoretti, S.; Vandin, F.; Wu, H.; et al. (Nature Publishing Group, 2013)
Genetic changes underlying clear cell renal cell carcinoma(ccRCC) include alterations in genes controlling cellularoxygen sensing (for example, VHL) and the maintenance of chromatin states (for example, PBRM1). We surveyed more than 400 tumours using different genomic platforms and identified 19 significantly mutated genes. The PI(3)K/AKT pathway was recurrently mutated, suggesting this pathway as a potential therapeutic target. Widespread DNA hypomethylation was associated with mutation of the H3K36 methyltransferase SETD2, and integrative analysis suggested that mutations involving the SWI/SNF chromatin remodelling complex (PBRM1, ARID1A, SMARCA4) could have far-reaching effects on other pathways. Aggressive cancers demonstrated evidence of a metabolic shift, involving downregulation of genes involved in the TCA cycle, decreasedAMPK and PTEN protein levels, upregulation of the pentose phosphate pathway and the glutamine transporter genes, increased acetyl-CoA carboxylase protein, and altered promoter methylation of miR-21 (also known as MIR21) and GRB10. Remodelling cellular metabolism thus constitutes a recurrent pattern in ccRCC that correlates with tumour stage and severity and offers new views on the opportunities for disease treatment. Â© 2013 Macmillan Publishers Limited. All rights reserved.